PENERAPAN MODEL PROBLEM BASED LEARNING BERBASIS GROWTH MINDSET UNTUK MENINGKATKAN HASIL BELAJAR DAN KETERLIBATAN AKTIF MURID PADA MATERI PENYAJIAN DATA KELAS III SDN 1 JATIPURO - Septiana Wijayanti; Tri Annisa Oktianah; Ratna Puspita Haryati; Rizqa Raudatul Jannah; Rohita Silvani; Ronallio Alip Fanindo; Siti Mariah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low mathematics achievement and limited active participation of third-grade students at SDN 1 Jatipuro, characterized by fear of making mistakes, lack of confidence, and teacher dominance in learning activities. The research aimed to improve learning outcomes while fostering a growth mindset, students’ courage to ask questions, willingness to attempt challenging tasks, and active participation in group discussions through the application of the Problem Based Learning (PBL) model with a growth mindset approach.The study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection across two cycles. The subjects were 20 third-grade students in the 2025/2026 academic year. Data were collected through growth mindset questionnaires, observation sheets of students’ active involvement, learning outcome tests, and documentation, and analyzed both quantitatively and qualitatively.Findings revealed that the growth mindset-based PBL model not only improved students’ mathematics achievement but also strengthened growth mindset indicators, namely the courage to ask questions, willingness to solve challenging problems, and active participation in discussions. The average score increased from 77.1 in the pre-cycle to 82 in Cycle I and 89 in Cycle II, while classical mastery rose from 65% to 80% and finally 100%. Observation data showed active involvement improved from 60% in the pre-cycle to 80% in Cycle I and 100% in Cycle II. Thus, the growth mindset-based PBL model proved effective in enhancing mathematics learning outcomes while shaping students into more active, confident, and resilient learners in third grade at SDN 1 Jatipuro.